Evaluation of water gargle samples for SARS‐CoV‐2 detection using Abbott ID NOW COVID‐19 assay. Issue 9 (18th May 2022) - Lévesque, Simon; Beauchemin, Stéphanie; Vallée, Maud; Longtin, Jean; Jacob‐Wagner, Mariève; Dumaresq, Jeannot; Dulcey, Carlos; Labbé, Annie‐Claude
Abstract: The Abbott ID NOW™ COVID‐19 assay has been shown as a reliable and sensitive alternative to reverse transcription‐polymerase chain reaction (RT‐PCR) testing from nasopharyngeal or nasal samples in symptomatic patients. Water gargle is an acceptable noninvasive alternative specimen for severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) detection by RT‐PCR. The objective of this study was to evaluate the performance of water gargle samples for the detection of SARS‐CoV‐2 using the ID NOW. Residual gargle samples were randomly selected among positive standard of care (SOC)‐nucleic acid amplification test (NAAT) samples. For testing on ID NOW, the manufacturer's instructions were followed, except for the specimen addition step: 500 µl of the gargle specimen was added to the blue sample receiver with a pipette and gently mixed. Among the 202 positive samples by SOC‐NAAT, 185 were positive by ID NOW (positive percent agreement [PPA]) = 91.6% (95% confidence interval [CI]: 86.9−95.0). For the 17 discordant samples, cycle threshold ( C t ) values were all ≥31.0. The PPA was significantly lower among asymptomatic patients (84.4%; 95% CI: 73.2−92.3) versus symptomatic patients (95.2%; 95% CI: 89.8−98.2). The performance of the ID NOW for the detection of SARS‐CoV‐2 infection on gargle samples is excellent when C t values are <31.0 and for patients that have COVID‐19 compatible symptoms.